Comparison of signalment and computed tomography findings in French Bulldogs, Pugs, and English Bulldogs with and without clinical signs associated with thoracic hemivertebra. (13th August 2019) - De Decker, Steven; Packer, Rowena M. A.; Cappello, Rodolfo; Harcourt‐Brown, Tom R.; Rohdin, Cecilia; Gomes, Sergio A.; Bergknut, Niklas; Shaw, Tom A.; Lowrie, Mark; Gutierrez‐Quintana, Rodrigo
Abstract: Background: Although thoracic hemivertebra can cause neurological signs, they occur commonly in neurologically normal dogs. Objectives: To evaluate whether computed tomography (CT) findings and factors associated with signalment can be used to differentiate between dogs with and without neurological signs associated with hemivertebra. Animals: One hundred sixty dogs with ≥1 hemivertebrae were retrospectively studied. This group consisted of 40 dogs with clinical signs caused by hemivertebra and 40 French Bulldogs, 40 Pugs, and 40 English Bulldogs that underwent CT for reasons unrelated to neurological disease. Methods: All dogs underwent CT and affected dogs also underwent magnetic resonance imaging. All CT studies were randomly evaluated by an observer blinded to signalment and clinical status. The following variables were evaluated: presence, number, location, and subtype of hemivertebra; presence of vertebral subluxation; severity of vertebral canal stenosis; presence, location, and severity of kyphosis, and number of vertebrae involved in the kyphotic segment. Statistical modeling was performed to identify factors associated with clinical status. Results: Pug breed (odds ration [OR], 10.8; P = .01), more severe kyphosis (OR, 1.1 per grade increase; P  < .001), fewer instead of more observed hemivertebrae (OR, 0.8; P = 0.03), and ventrolateral hypoplasia hemivertebra subtype (OR, 4.0; P = .011) were associated with higher likelihood of neurological disease. A Cobb angle of 34.5 degrees corresponded with the highest combined sensitivity and specificity to differentiate between clinically affected and unaffected dogs. Conclusions and Clinical Importance: The variables identified could aid in differentiating between clinically relevant and irrelevant hemivertebra in small breed brachycephalic dogs.